Characterization of biosecurity system in poultry farms, in the municipality of Chinácota, Norte de Santander - Solano Rojas, Rito Arnulfo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of this study is to quantify the biosecurity aspects that poultry farms present in the municipality of Chinácota must comply with. Initially in the investigation, the poultry farms in the municipality of Chinácota were identified, giving a total of 128 farms, classified as 41 registered with the Colombian Agricultural Institute (ICA) and 87 not registered, of these, a representative sample of 30 was selected. % of each group equivalent to 38 poultry farms distributed in 12 registered and 26 not registered with the ICA. Two instruments were used to collect information, the checklist technique, the method of analysis with the statistical package Spss21 and analysis of the results through the use of graphs or tables; To determine the internal reliability of the checklist, the Kuder Richarson was applied; Finally, the actors' triangulation was carried out. The results obtained by instrument 1 (check list) showed that 50% (19 farms) of the sample meet the established requirements; in the specific items, there is a 40% compliance on average. As for the instrument 2 (Evaluation of socio-economic factors), the lack of knowledge, training, accompaniment to producers and the economic factor for the implementation of biosafety systems can be highlighted as the main limiting factor. Finally, the information was analyzed and interpreted, considering pertinent measures that improve the adoption of the biosecurity system at the farm level, generating a product with quality and safety.